2021
DOI: 10.3390/genes12060932
|View full text |Cite
|
Sign up to set email alerts
|

Increase in Phloem Area in the Tomato hawaiian skirt Mutant Is Associated with Enhanced Sugar Transport

Abstract: The Hawaiian skirt (HWS) gene has been described in Arabidopsis, rice, tomato and poplar where it seems to perform distinct functions with relatively little overlap. In tomato, alteration of the gene function confers facultative parthenocarpy, thought to be a consequence of changes in the microRNA metabolism. In the rice mutant, improvement in panicle architecture is associated with an increase in grain yield. Knowing that hws tomato fruits show a higher Brix level, it was suspected that vascular bundles might… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Such investigations might be strengthened through including phloem development mutants (e.g. Lombardo et al ., 2021; Nam et al ., 2022). Do plasmodesmata located at se‐ccc/vascular parenchyma interfaces regulate sucrose import into developing seeds?…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such investigations might be strengthened through including phloem development mutants (e.g. Lombardo et al ., 2021; Nam et al ., 2022). Do plasmodesmata located at se‐ccc/vascular parenchyma interfaces regulate sucrose import into developing seeds?…”
Section: Discussionmentioning
confidence: 99%
“…Such investigations might be strengthened through including phloem development mutants (e.g. Lombardo et al, 2021;Nam et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In tomato, Li et al (2021) found that the water deficit did not change the hydraulic resistance and the vascular structure in the pedicel; however, this could not provide any clue about how the structural differences of vascular affect the hydraulic transport in the plant. A mutant tomato ( hws-1 ) with wider phloem and narrower xylem rings showed a higher sugar concentration in the phloem exudates and a higher Brix level in the fruit, indicating that the increased phloem area ratio contributes to the higher fruit Brix in tomatoes ( Lombardo et al, 2021 ). In grape, Shigyoku ( Vitis vinifera ) showed 1.8-fold greater phloem area of the pedicel than that of Heukboseok ( V. vinifera ) after veraison, based on the number of cells constituting the phloem, whereas no difference of xylem area was found between them; the cell number and area of the phloem contributed to the accumulation of sugars and the main constituents of the cell wall, thus maintaining the firmness of grapes until late maturity; therefore, the phloem structure was considered to contribute to the increased softening of Heukboseok grapes ( Jung et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Two recent reviews have suggested that improving phloem loading or unloading could be an avenue to improve crop yield (Braun et al, 2014; Reynolds et al, 2021). In several species including rice, phloem transport capacity has been suggested to play a role in grain, seed or fruit production (Deng et al, 2021; Lombardo et al, 2021; Nam et al, 2022; You et al, 2021; Zhai et al, 2023). To our knowledge, there is no overview of phloem transport properties amongst wheat cultivars and thus potential relationships with yield are not well known.…”
Section: Introductionmentioning
confidence: 99%